Prestroke Antihypertensive Therapy: Effect on the Outcome. (April 2013) - Grabska, Katarzyna; Gromadzka, Grażyna; Członkowska, Anna
<x xml:space="preserve">Abstract</x> About 70% of stroke patients have a history of hypertension. Patients with hypertension prior to stroke onset have higher blood pressure in the acute phase of stroke than non-hypertensive individuals. High blood pressure in the acute stroke adversely affects outcome. We analyzed 30-days outcome in 1306 hypertensive patients with ischemic stroke, of which 1069 (81.8%) received antihypertensive treatment before stroke onset. Multivariate logistic regression revealed that prestroke use of antihypertensives is an independent predictor of better stroke outcome, in terms of dependency and death or dependency. We conclude that increased efforts toward optimizing hypertension diagnostics and control are needed.